2022
DOI: 10.3389/fgene.2022.949241
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster: A platform for anticancer drug discovery and personalized therapies

Abstract: Cancer is a complex disease whereby multiple genetic aberrations, epigenetic modifications, metabolic reprogramming, and the microenvironment contribute to the development of a tumor. In the traditional anticancer drug discovery pipeline, drug candidates are usually screened in vitro using two-dimensional or three-dimensional cell culture. However, these methods fail to accurately mimic the human disease state. This has led to the poor success rate of anticancer drugs in the preclinical stages since many drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 142 publications
0
11
0
Order By: Relevance
“…These factors, in addition to the advancement of genetic toolkits for manipulating gene expression, allow for the generation of complex Drosophila genotypes and phenotypes. [33] Scribble (scrib) is a cell polarity determinant in Drosophila and humans. Disruption in cell polarity paves the way for neoplastic cancer progression.…”
Section: In-vivo Anti-cancer Studiesmentioning
confidence: 99%
“…These factors, in addition to the advancement of genetic toolkits for manipulating gene expression, allow for the generation of complex Drosophila genotypes and phenotypes. [33] Scribble (scrib) is a cell polarity determinant in Drosophila and humans. Disruption in cell polarity paves the way for neoplastic cancer progression.…”
Section: In-vivo Anti-cancer Studiesmentioning
confidence: 99%
“…With its sophisticated genetic tools and practical advantages, Drosophila has a strong track record as a disease model and has also emerged as a useful drug discovery platform ( Cheng et al 2018 ; Mohr and Perrimon 2019 ; Munnik et al 2022 ). Disease models generated either by genetically manipulating Drosophila orthologs of human disease genes or directly introducing disease-associated variants of human genes into Drosophila have provided important insights into molecular mechanisms underlying human diseases, including cancer ( Verheyen 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disease models generated either by genetically manipulating Drosophila orthologs of human disease genes or directly introducing disease-associated variants of human genes into Drosophila have provided important insights into molecular mechanisms underlying human diseases, including cancer ( Verheyen 2022 ). Furthermore, multiple studies over the past decade have demonstrated a high degree of conservation of compound activity in Drosophila ( Su 2019 ; Munnik et al 2022 ); several compounds identified through these studies have been effective in vertebrate experimental models and human patients ( Dar et al 2012 ; Bangi et al 2016 , 2019 , 2021 ; Das et al 2018 ; Sonoshita et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila, with its sophisticated genetic tools and practical advantages, has a strong track record as a disease model and has also emerged as a useful drug discovery platform (Cheng et al . 2018; Mohr and Perrimon 2019; Munnik et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Disease models generated either by genetically manipulating Drosophila orthologs of human disease genes or directly introducing disease associated variants of human genes into Drosophila have provided important insights into molecular mechanisms underlying human diseases including cancer (Verheyen 2022). Furthermore, multiple studies over the past decade have demonstrated a high degree of conservation of compound activity in Drosophila (Su 2019; Munnik et al . 2022); several compounds identified through these studies have been effective in vertebrate experimental models and human patients (Dar et al .…”
Section: Introductionmentioning
confidence: 99%